Laminate and paper processed article using same

By forming a laminated structure on the paper substrate, using a barrier layer of polyurethane resin, flat inorganic compounds and cationic resin, and combining a sealant layer of wax, the existing paper substrate has solved the shortcomings in both gas barrier and water vapor barrier properties, and achieved efficient water vapor barrier and gas barrier effects, while improving the biomass ratio of the paper and reducing the negative impact on the environment.

CN119604415APending Publication Date: 2025-03-11OJI HLDG CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380056319.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-07-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

There are shortcomings in both gas barrier properties and water vapor barrier properties of existing paper substrates to a higher extent, and there are environmental problems with traditional use of synthetic resin films.

Method used

A laminated body structure is adopted, which includes a paper base layer, a barrier layer and a sealant layer in sequence. The barrier layer is composed of polyurethane resin, a flat inorganic compound and a cationic resin. The sealant layer contains wax, and the water vapor barrier and gas barrier properties are improved through the combination of these materials.

Benefits of technology

It achieves a high degree of consideration of water vapor barrier properties and gas barrier properties, improves paper ratio (biomass ratio), reduces the amount of film used, and has better environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257050610000301
    Figure BDA0005257050610000301
  • Figure BDA0005257050610000311
    Figure BDA0005257050610000311
  • Figure BDA0005257050610000312
    Figure BDA0005257050610000312
Patent Text Reader

Abstract

Provided is a laminate which has a high level of both water vapor barrier properties and gas barrier properties, and which can further improve the paper ratio (biomass ratio). A laminate provided with a paper substrate layer, a barrier layer, and a sealant layer in this order, the barrier layer containing a urethane resin, a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more, and a cationic resin, and the sealant layer containing a wax.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a laminate having barrier properties and a paper processed product using the laminate. Background Art

[0002] In order to prevent the quality of the contents from being degraded, etc., packaging materials having gas barrier properties such as oxygen barrier properties and water vapor barrier properties imparted to paper substrates have been used in the past.

[0003] As a method for imparting water vapor barrier properties and gas barrier properties to a paper substrate, a method of laminating a synthetic resin film or the like having excellent gas barrier properties on the paper substrate is generally used. However, materials in which a synthetic resin film or the like is laminated on a paper substrate are difficult to recycle the paper, synthetic resin, etc. after use, which poses an environmental problem.

[0004] Therefore, the development of gas barrier materials based on paper instead of synthetic resin films has been gradually promoted. For example, Japanese Patent Publication No. 2021-138434 describes a technology for controlling the hydroxyl group and acid group of the resin used in the gas barrier layer in a paper barrier material in which a gas barrier layer and a heat seal layer are sequentially provided on a paper substrate. Summary of the invention

[0005] The paper barrier material described in Japanese Patent Application Laid-Open No. 2021-138434 has a single-layer barrier layer, which can reduce the amount of plastic material. However, it is not sufficient from the perspective of achieving a higher degree of gas barrier properties and achieving both gas barrier properties and water vapor barrier properties.

[0006] The present disclosure provides a laminate that can achieve both water vapor barrier properties and gas barrier properties at a high level and further improve the paper ratio (biomass ratio).

[0007] The present disclosure relates to the following <1> to <18>.

[0008] <1> A laminate comprising: a paper base layer, a barrier layer, and a sealant layer in this order, wherein the barrier layer comprises a polyurethane resin, a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more, and a cationic resin, and the sealant layer comprises wax.

[0009] <2> The laminate according to <1>, wherein the polyurethane resin includes at least one selected from the group consisting of a polyurethane having a structural unit derived from meta-xylylene isocyanate and a hydroxy polyurethane.

[0010] <3> The laminate according to <1> or <2>, wherein the flat inorganic compound includes a swelling layered silicate.

[0011] <4> The laminate according to any one of <1> to <3>, wherein the barrier layer contains 1.0 to 20.0% by mass of the cationic resin.

[0012] <5> The laminate according to any one of <1> to <4>, wherein the barrier layer contains 30.0 to 80.0% by mass of the polyurethane resin.

[0013] <6> The laminate according to any one of <1> to <5>, wherein the barrier layer contains 5.0 to 35.0% by mass of the flat inorganic compound.

[0014] <7> The laminate according to any one of <1> to <6>, wherein the barrier layer further comprises at least one selected from the group consisting of a water-suspended polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, the water-suspended polymer comprising at least one selected from the group consisting of a styrene-butadiene copolymer, a styrene-acrylic acid copolymer, an olefin-unsaturated carboxylic acid copolymer and a polyolefin resin, and the water-soluble polymer comprising at least one selected from the group consisting of a vinyl alcohol polymer and a (meth)acrylic acid polymer.

[0015] <8> The laminate according to any one of <1> to <6>, wherein the barrier layer further comprises at least one of a water-suspended polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, and the barrier layer comprises the water-suspended polymer and the water-soluble polymer in any combination of at least the following (A) to (E).

[0016] (A) Water-suspended polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol.

[0017] (B) Water-suspended polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyacrylic acid.

[0018] (C) Water-suspendable polymer: styrene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol.

[0019] (D) Water-suspendable polymer: styrene-butadiene copolymer, water-soluble polymer: polyvinyl alcohol.

[0020] (E) Water-suspended polymer: polyolefin resin, water-soluble polymer: polyvinyl alcohol.

[0021] <9> The laminate according to <7> or <8>, wherein the barrier layer contains 1.0 to 50.0% by mass in total of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin.

[0022] <10> The laminate according to any one of <7> to <9>, wherein the ratio of the mass of the polyurethane resin in the barrier layer to the total mass of the water-suspended polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin (mass of the polyurethane resin: total mass of the water-suspended polymer and the water-soluble polymer) is 50:50 to 95:5.

[0023] <11> The laminate according to any one of <1> to <10>, wherein the sealant layer contains a water-dispersible resin.

[0024] <12> The laminate according to any one of <1> to <11>, wherein the wax includes at least one selected from the group consisting of hydrocarbon waxes and ester waxes.

[0025] <13> The laminate according to any one of <1> to <12>, wherein the wax includes at least one selected from the group consisting of paraffin wax, carnauba wax, and microcrystalline wax.

[0026] <14> The laminate according to any one of <1> to <13>, wherein the sealant layer contains a water-dispersible resin containing at least one selected from the group consisting of a styrene-acrylic acid-based copolymer and a polyolefin resin.

[0027] <15> The laminate according to any one of <1> to <14>, wherein the sealant layer contains a water-dispersible resin, and the sealant layer contains the water-dispersible resin and the wax in at least any combination of the following (A) to (D).

[0028] (A) Water-dispersible resin: styrene-acrylic acid copolymer, wax: paraffin wax.

[0029] (B) Water-dispersible resin: styrene-acrylic acid copolymer, wax: carnauba wax.

[0030] (C) Water-dispersible resin: styrene-acrylic acid copolymer, wax: microcrystalline wax.

[0031] (D) Water-dispersible resin: polyolefin resin, wax: paraffin wax.

[0032] <16> The laminate according to any one of <1> to <15>, wherein the sealant layer contains a water-dispersible resin, and the content of the wax in the sealant layer is 1 to 35 parts by mass based on 100 parts by mass of the water-dispersible resin.

[0033] <17> The laminate according to any one of <1> to <16>, wherein a content of the wax in the sealant layer is 1 to 30% by mass.

[0034] <18> A processed paper product, comprising the laminate according to any one of <1> to <17>. DETAILED DESCRIPTION

[0035] In this specification, "X to Y" indicating a range means "above X and below Y". When the numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In this specification, unless otherwise specified, "gas barrier properties" means "oxygen barrier properties". In addition, in this specification, (meth)acrylic acid is a general term for acrylic acid and methacrylic acid. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are carried out under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.

[0036] One embodiment of the present disclosure relates to a laminate, which comprises a paper substrate layer, a barrier layer and a sealant layer in sequence, wherein the barrier layer comprises a polyurethane resin, a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more, and a cationic resin, and the sealant layer comprises wax. The laminate can achieve both water vapor barrier properties and gas barrier properties to a high degree, and further improve the paper ratio (biomass ratio). The mechanism of exerting this effect is not clear, but it is speculated as follows.

[0037] The barrier layer contains a polyurethane resin, a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more, and a cationic resin. The present inventors believe that by making the barrier layer contain the above materials, especially by using the flat inorganic compound and the cationic resin having the above characteristics in combination, the maze effect obtained by the flat inorganic compound described below can be effectively exerted, and high water vapor barrier properties and gas barrier properties can be exerted.

[0038] In addition, the sealant layer contains wax, which can exert excellent water vapor barrier properties. The inventors of the present invention believe that this is due to the film-forming effect of the wax. Specifically, it is believed that the wax floats on the surface of the sealant layer during coating, melts due to heat, forms a film, and covers the surface of the sealant layer, thereby exerting excellent water vapor barrier properties.

[0039] The combination of these specific barrier layers and sealant layers can achieve both water vapor barrier properties and gas barrier properties to a high degree. In addition, the above-mentioned laminate can exert a higher degree of water vapor barrier properties and gas barrier properties, so compared with existing barrier laminates, the amount of film used can be greatly reduced and the paper ratio (biomass ratio) can be increased.

[0040] It should be noted that the effects of the present invention are not limited to the above-mentioned mechanism.

[0041] The laminate of the present embodiment may have the barrier layer and the heat seal layer in this order only on one side of the paper base layer, or may have the barrier layer and the heat seal layer in this order on both sides of the paper base layer.

[0042] Hereinafter, each structure of the laminate will be described.

[0043] <Paper base layer>

[0044] The laminate includes a paper substrate layer. The paper substrate used in the paper substrate layer is not particularly limited, and a known paper material can be used.

[0045] The pulp constituting the paper substrate preferably has plant-derived pulp as the main component, and wood pulp as the main component. Examples of wood pulp include hardwood pulp and coniferous wood pulp. Examples of non-wood pulp include cotton pulp, hemp pulp, kenaf pulp, and bamboo pulp. Unless the effects of the present invention are impaired, materials other than pulp fibers such as synthetic fibers such as rayon fibers and nylon fibers may be used as the secondary paper material.

[0046] Specific examples of the paper substrate include bleached kraft paper, unbleached kraft paper, fine paper, cardboard, liner, coated paper, single gloss white kraft paper, glassine, and Grafan paper, etc. Among them, bleached kraft paper, unbleached kraft paper, fine paper, and single gloss white kraft paper are preferred, bleached kraft paper and glossy paper are more preferred, and single gloss white kraft paper is further preferred.

[0047] The paper substrate may also contain additives. Examples of additives include pH adjusters (sodium bicarbonate, sodium hydroxide, etc.), dry strength agents (polyacrylamide, starch, etc.), wet strength agents (polyamide polyamine epichlorohydrin resin, melamine-formaldehyde resin, urea-formaldehyde resin), internal sizing agents (rosin, alkyl ketene dimer, etc.), retention and drainage aids, defoamers, fillers (calcium carbonate, talc, etc.), dyes, etc. These additives may be used alone or in combination of two or more. The content of the additives is not particularly limited and may be within the range commonly used.

[0048] (Weight per unit area)

[0049] The weight per unit area of ​​the paper substrate can be appropriately changed according to the purpose of use of the laminate and is not particularly limited. For example, if it is used for packaging bags, it is preferably 20 g / m 2 Above and 150g / m 2 Below, more preferably 30g / m 2 Above and 100g / m 2 Below, more preferably 40g / m 2 Above and 70g / m 2The basis weight of the paper substrate is measured in accordance with JIS P 8124:2011.

[0050] (Paper thickness)

[0051] The thickness of the paper substrate can be appropriately changed according to the purpose of use of the laminate, and is not particularly limited. For example, if it is used for packaging bags, it is preferably 20 μm or more and 150 μm or less, more preferably 25 μm or more and 100 μm or less, and further preferably 30 μm or more and 50 μm or less. The thickness of the paper substrate is measured in accordance with JIS P8118:2014.

[0052] (Wang Yan type smoothness)

[0053] The smoothness of the paper substrate is not particularly limited. For example, the surface on the side where the barrier layer is provided preferably has a Wohnen smoothness of 5 seconds or more, more preferably 10 seconds or more. The upper limit is not particularly limited, but for example, it is preferably 2000 seconds or less, more preferably 1000 seconds or less. It should be noted that the Wohnen smoothness of the paper substrate is measured in accordance with JIS P 8155:2010.

[0054] (Method for producing paper substrate)

[0055] As a method for manufacturing a paper substrate, a method of making paper from a paper stock containing pulp can be cited. It should be noted that the paper stock may further contain additives. As additives, for example, the additives cited above can be cited.

[0056] The paper stock can be prepared by adding an additive to a pulp slurry. The pulp slurry is obtained by beating pulp in the presence of water. The pulp beating method and the beating device are not particularly limited, and can be the same as the known beating method and beating device. The content of the pulp in the paper stock is not particularly limited, and can be within the range commonly used. For example, it is 60% by mass or more and less than 100% by mass relative to the total mass of the paper stock.

[0057] Papermaking of paper stock can be carried out by conventional methods. For example, the following methods can be cited: casting the paper stock on a wire or the like, dehydrating to obtain wet paper, overlapping multiple wet paper sheets as needed, pressing the single-layer or multi-layer wet paper sheets, and drying them. In this case, a single-layer paper can be obtained when multiple wet paper sheets are not overlapped, and a multi-layer paper can be obtained when multiple wet paper sheets are overlapped. When overlapping multiple wet paper sheets, an adhesive can also be applied to the surface of the wet paper (the surface overlapping other wet paper sheets).

[0058] <Barrier layer>

[0059] The laminate has a barrier layer. For example, the laminate preferably has a barrier layer on at least one side of the paper substrate. The barrier layer may be one layer or two or more layers, but is preferably one layer (single layer) from the perspective of manufacturing cost. The barrier layer exhibits high water vapor barrier properties and gas barrier properties as described above.

[0060] (Polyurethane resin)

[0061] The barrier layer contains a polyurethane resin. The polyurethane resin is not particularly limited as long as it is a polymer having a urethane bond, and a known polyurethane resin can be used.

[0062] From the viewpoint of taking into account both water vapor barrier properties and gas barrier properties to a higher degree, the polyurethane resin preferably includes at least one selected from the group consisting of polyurethane having a structural unit derived from meta-xylylene diisocyanate and hydroxy polyurethane, and more preferably includes hydroxy polyurethane. Polyurethane resin is usually obtained by the reaction of polyisocyanate with a polyol having two or more hydroxyl groups, and "polyurethane having a structural unit derived from meta-xylylene diisocyanate" means a polyurethane resin obtained by the above reaction using a part or all of meta-xylylene diisocyanate as a polyisocyanate. In addition, "hydroxy polyurethane" refers to a polyurethane resin having a hydroxyl group.

[0063] The hydroxy value of the hydroxy polyurethane is preferably 100 to 500 mgKOH / g, more preferably 150 to 400 mgKOH / g, and even more preferably 200 to 350 mgKOH / g. The above hydroxy value improves the cohesive force of the hydroxy polyurethane and makes it easier to exhibit high barrier properties.

[0064] The hydroxy polyurethane may have an acid group. The acid value of the hydroxy polyurethane is preferably 50 to 100 mgKOH / g, more preferably 10 to 70 mgKOH / g, and further preferably 15 to 60 mgKOH / g.

[0065] The acid value and hydroxy value of hydroxy polyurethane can be measured by a titration method in accordance with JIS K 1557:2007.

[0066] In the case where the polyurethane resin has a structural unit derived from meta-xylylene isocyanate, the content of the structural unit derived from meta-xylylene isocyanate is preferably 50 mol% or more relative to the total amount of the structural unit derived from polyisocyanate. Such a polyurethane resin exhibits high cohesion due to hydrogen bonding and the stacking effect of xylene groups, and is therefore considered to have better gas barrier properties. The above content can be used 1 The identification was carried out by a known analytical method such as H-NMR.

[0067] The glass transition temperature of the polyurethane resin is preferably 50° C. or higher, more preferably 65° C. or higher, further preferably 90° C. or higher, and further preferably 110° C. or higher. The upper limit is not particularly limited, but is, for example, 200° C. or lower. The glass transition temperature of the polyurethane resin is a value measured in accordance with JIS K 7121:1987.

[0068] As the hydroxy polyurethane, commercially available hydroxy polyurethane can be used. For example, HPU W-001, HPU W-003, HPU-W013A (all manufactured by Dainichi Seika Industries, Ltd.) and the like can be cited. In addition, as a polyurethane having a structural unit derived from meta-xylylene diisocyanate, TAKELAC WPB-341 (30) (manufactured by Mitsui Chemicals, Inc.) and the like can be cited.

[0069] The content of the polyurethane resin (preferably hydroxy polyurethane) in the barrier layer is preferably 30.0 to 80.0% by mass, more preferably 40.0 to 75.0% by mass, further preferably 50.0 to 70.0% by mass, further preferably 55.0 to 68.0% by mass, and further preferably 60.0 to 66.0% by mass. By being within the above range, it is easy to further improve the water vapor barrier and gas barrier properties. In addition, if it is within the above range, the strength of the barrier layer is good, and when a heat seal layer is provided on the barrier layer, the heat sealability is good.

[0070] The barrier layer may contain other resins in addition to the polyurethane resin to the extent that the above-mentioned effects are not impaired. The other resins are not particularly limited, and examples thereof include polyolefin resins (polyethylene, polypropylene, etc.), vinyl chloride resins, styrene resins, styrene / butadiene copolymers, acrylonitrile / styrene copolymers, acrylonitrile / butadiene copolymers, ABS (acrylonitrile butadiene styrene: acrylonitrile / butadiene / styrene) resins, AAS (acrylonitrileacrylate styrene: acrylonitrile / acrylate / styrene) resins, AES (acrylonitrile ethylenepropylene rubbers Styrene: acrylonitrile / ethylene-propylene rubber / styrene) resin, vinylidene chloride resin, poly-4-methylpentene-1 resin, polybutene-1 resin, vinylidene fluoride resin, vinyl fluoride resin, fluororesin, polycarbonate resin, acetal resin, polyphenylene ether resin, polyester resin (polyethylene terephthalate, polybutylene terephthalate, etc.), polyphenylene sulfide resin, polyimide resin, polysulfone resin, polyethersulfone resin, aromatic polyester resin, polyarylate resin, olefin / unsaturated carboxylic acid copolymer, styrene / unsaturated carboxylic acid copolymer, acrylic resin, polyvinyl alcohol and its modified resin, polyacrylic acid and its salt, cellulose derivatives, starch and its derivatives and other polysaccharide resins, natural rubber, shellac and other natural thermosetting resins and their modified products, etc. These resins may be used alone or in combination of two or more.

[0071] (Water-suspended polymer, water-soluble polymer)

[0072] The barrier layer preferably contains at least one selected from the group consisting of a water-suspended polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, in addition to the polyurethane resin, the flat inorganic compound and the cationic resin. The water-suspended polymer and the water-soluble polymer can be selected from the above-mentioned resins as other resins that can be used for the barrier layer.

[0073] The water-suspendable polymer other than the polyurethane resin preferably includes at least one selected from the group consisting of styrene-butadiene copolymers, styrene-acrylic acid copolymers, olefin-unsaturated carboxylic acid copolymers and polyolefin resins. The water-suspendable polymer may be used alone or in combination of two or more.

[0074] As water-soluble polymers other than polyurethane resins, vinyl alcohol polymers, polyalkylene imines, (meth) acrylic acid polymers, polyethylene glycol, polyacrylamide, polycarboxylic acids, water-soluble cellulose derivatives, etc. can be listed, preferably including at least one selected from the group consisting of vinyl alcohol polymers and (meth) acrylic acid polymers. The water-soluble polymers can be used alone or in combination of two or more.

[0075] According to the research of the present inventors, it is known that the three components of polyurethane resin, flat inorganic compound and cationic resin are good in barrier properties, but are not sufficient from the perspective of the film-forming property of the barrier layer. Therefore, the present inventors found that by adding water-suspended polymers and water-soluble polymers to the three components of polyurethane resin, flat inorganic compound and cationic resin, the film-forming property of the barrier layer is improved, and as a result, the water vapor barrier property and gas barrier property are further improved. Hereinafter, water-suspended polymers and water-soluble polymers other than polyurethane resin are collectively referred to as film-forming aids.

[0076] In the case of forming a barrier layer by water-based coating, water-soluble polymers have an excellent effect of improving film-forming properties compared to water-suspended polymers. Moreover, from the perspective of improving the water resistance of the barrier layer and making the water vapor barrier property better, it is preferred to use a water-suspended polymer on the basis of a water-soluble polymer. That is, the barrier layer preferably contains a water-suspended polymer and a water-soluble polymer. At this time, as a water-suspended polymer, an olefin-unsaturated carboxylic acid copolymer is preferred, and an ethylene-(meth)acrylic acid copolymer is more preferred. In addition, as a water-soluble polymer, a vinyl alcohol polymer is preferred. By adopting the combination of the above-mentioned water-suspended polymer and the water-soluble polymer, water vapor barrier properties and gas barrier properties can be taken into account to a higher degree.

[0077] The mass ratio of the water-suspendable polymer to the water-soluble polymer in the barrier layer (water-suspendable polymer: water-soluble polymer) is preferably 20:1 to 1:2, more preferably 10:1 to 2:3, further preferably 5:1 to 3:4, and further preferably 4:1 to 4:5.

[0078] The barrier layer preferably contains a water-suspendable polymer and a water-soluble polymer. In this case, the barrier layer preferably contains a water-suspendable polymer and a water-soluble polymer in a combination of at least any of the following (A) to (E).

[0079] (A) Water-suspendable polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol.

[0080] (B) Water-suspended polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyacrylic acid.

[0081] (C) Water-suspendable polymer: styrene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol.

[0082] (D) Water-suspendable polymer: styrene-butadiene copolymer, water-soluble polymer: polyvinyl alcohol.

[0083] (E) Water-suspended polymer: polyolefin resin, water-soluble polymer: polyvinyl alcohol.

[0084] (Water-suspended polymer)

[0085] 《Styrene-butadiene copolymer》

[0086] Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, chlorostyrene, etc., butadiene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc., and other compounds copolymerizable with them.

[0087] As the styrene-based compound, styrene is preferred, and as the butadiene-based compound, 1,3-butadiene is preferred.

[0088] As the styrene-butadiene copolymer, a commercially available styrene-butadiene copolymer may be used. For example, as an acid-modified styrene-butadiene copolymer adhesive, LX407S12 (manufactured by ZEON Corporation of Japan) and the like are exemplified.

[0089] 《Styrene-acrylic copolymer》

[0090] Styrene-acrylic acid copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, and chlorostyrene and acrylic acid compounds such as acrylic acid, methacrylic acid, (meth)acrylic acid esters, (meth)acrylamide propanesulfonic acid, (meth)acrylic acid sulfoalkyl ester sodium salt (the number of carbon atoms of the alkyl group is 2 or more and 3 or less), and other compounds copolymerizable with them. As the styrene compound, styrene is preferred, and as the acrylic acid compound, acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are preferred, and acrylic acid and acrylic acid esters are more preferred. As the (meth)acrylic acid esters, acrylic acid alkyl esters are preferred, and the number of carbon atoms of the alkyl group is preferably 1 to 6.

[0091] As the styrene-acrylic acid-based copolymer, a commercially available styrene-acrylic acid-based copolymer may be used. For example, as a styrene-acrylic acid copolymer adhesive, JONCRYL HSL-9012 (manufactured by BASF) and the like are exemplified.

[0092] 《Olefin-unsaturated carboxylic acid copolymer》

[0093] The olefin-unsaturated carboxylic acid copolymer is a copolymer obtained by emulsion polymerization of monomers consisting of an olefin, especially an α-olefin such as propylene or ethylene, and an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenetricarboxylic acid, an unsaturated polycarboxylic acid alkyl ester having at least one carboxyl group such as monoethyl itaconate, monobutyl fumarate and monobutyl maleate, and other compounds copolymerizable with them.

[0094] As the olefin, ethylene or α-olefin is preferred, and ethylene is more preferred. In addition, as the unsaturated carboxylic acid monomer, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, etc. are preferred.

[0095] As the olefin-unsaturated carboxylic acid-based copolymer, an ethylene-(meth)acrylic acid copolymer is preferred, and an ethylene-acrylic acid copolymer is more preferred.

[0096] Specific examples of olefin-unsaturated carboxylic acid copolymers include aqueous dispersions of ethylene-acrylic acid copolymer ammonium salts, which are commercially available as ZAIKTHENE (registered trademark) AC (acrylic acid copolymerization ratio: 20%, manufactured by Sumitomo Seika Chemicals Co., Ltd.), and are easily available and usable.

[0097] 《Polyolefin resin》

[0098] As the polyolefin resin, a homopolymer or copolymer of a monomer selected from the group consisting of ethylene and α-olefins is preferred, and polyethylene is more preferred. Commercially available polyolefins may also be used as the polyolefin. For example, HYDRECT HS (manufactured by DIC Corporation) and the like may be cited as the polyolefin resin adhesive.

[0099] (Water-soluble polymer)

[0100] 《Vinyl alcohol polymers》

[0101] As the vinyl alcohol polymer, polyvinyl alcohol can be cited. The saponification degree of the polyvinyl alcohol is preferably 85.0 to 99.5 mol%, more preferably 90.0 to 99.0 mol%. In addition, alkyl-modified polyvinyl alcohols such as ethylene-modified polyvinyl alcohol are preferred. Commercially available polyvinyl alcohols can also be used as polyvinyl alcohols. For example, EXCEVAL series (manufactured by Kuraray Co., Ltd.) can be cited.

[0102] 《(Meth)acrylic acid polymers》

[0103] Examples of the (meth)acrylic acid polymer include polyacrylic acid, polymethacrylic acid, and salts thereof. Examples of the salt include sodium poly(meth)acrylate and ammonium poly(meth)acrylate. Commercially available (meth)acrylic acid polymers may also be used. For example, an aqueous solution of ammonium polyacrylate may include Aron A-30 (manufactured by Toagosei Co., Ltd.).

[0104] In addition, as the water-soluble polymer, known polyethylene glycol, water-soluble polyamide, polyacrylamide, polycarboxylic acid and water-soluble cellulose derivatives can be used. Examples of polycarboxylic acids include polymaleic acid, acrylic acid maleic acid copolymer, polyglucuronic acid, etc. These can be used alone or in combination of two or more.

[0105] Examples of the water-soluble cellulose derivatives include methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, and methyl hydroxyethyl cellulose.

[0106] The weight average molecular weight of the water-suspendable polymer and the water-soluble polymer is preferably 10,000 or more, more preferably 20,000 or more, and preferably 10 million or less, more preferably 5 million or less. The weight average molecular weight of the water-suspendable polymer is measured using gel permeation chromatography (standard substance: polystyrene). The weight average molecular weight of the water-soluble polymer is measured using gel permeation chromatography (standard substance: polyethylene glycol).

[0107] The total content of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin in the barrier layer is preferably 1.0 to 50.0% by mass, more preferably 5.0 to 45.0% by mass, further preferably 10.0 to 35.0% by mass, and further preferably 13.0 to 25.0% by mass. Within the above range, it is easy to further improve the water vapor barrier and gas barrier properties, and the heat sealability is also better.

[0108] The content of the water-suspendable polymer other than the polyurethane resin in the barrier layer is preferably 1.0 to 40.0% by mass, more preferably 5.0 to 30.0% by mass, further preferably 8.0 to 20.0% by mass, and further preferably 10.0 to 15.0% by mass. Within the above range, the water vapor barrier property and the gas barrier property are easily improved, and the heat sealability is also improved.

[0109] The content of the water-soluble polymer other than the polyurethane resin in the barrier layer is preferably 1.0 to 20.0% by mass, more preferably 2.0 to 15.0% by mass, further preferably 2.0 to 10.0% by mass, further preferably 3.0 to 8.0% by mass, and further preferably 3.5 to 6.0% by mass. Within the above range, it is easy to further improve the water vapor barrier property and the gas barrier property (especially the oxygen barrier property under high humidity), and the heat sealability is also further improved.

[0110] From the viewpoint of achieving both barrier properties (especially gas barrier properties) and film-forming properties, the mass ratio of the polyurethane resin to the film-forming aid (the total of water-suspended polymers other than the polyurethane resin and water-soluble polymers other than the polyurethane resin) in the barrier layer (polyurethane resin: film-forming aid) is preferably 50:50 to 95:5, more preferably 55:45 to 90:10, further preferably 60:40 to 85:15, and further preferably 70:30 to 85:15.

[0111] (Flat inorganic compound)

[0112] In order to easily improve the water vapor barrier property and the gas barrier property, the barrier layer contains a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more. The flat inorganic compound is, for example, in the form of a plate.

[0113] By using a flat inorganic compound in the barrier layer, the flat inorganic compound is easily stacked roughly parallel to the plane (surface) of the paper substrate. In this way, the area where the flat inorganic compound does not exist in the plane direction will become smaller, so it is easy to suppress the permeation of water vapor. In addition, in the thickness direction, the flat inorganic compound exists in a manner arranged parallel to the plane of the paper substrate, so the water vapor in the layer passes through while bypassing the flat inorganic compound, and the maze effect is used to suppress the permeation of water vapor. As a result, the barrier layer easily exhibits excellent water vapor barrier properties.

[0114] The average thickness of the flat inorganic compound is 50 nm or less. The average thickness of the flat inorganic compound is preferably 30 nm or less, more preferably 20 nm or less, further preferably 15 nm or less, and particularly preferably 10 nm or less. The smaller the thickness of the flat inorganic compound, the greater the number of layers of the flat inorganic compound in the barrier layer, and thus a high water vapor barrier property can be exerted. The lower limit of the thickness of the flat inorganic compound is not particularly limited, but is preferably 0.5 nm or more, more preferably 1 nm or more, and further preferably 2 nm or more.

[0115] Here, the average thickness of the flat inorganic compound in the state of being contained in the barrier layer is calculated as follows. An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set to include about 20 to 30 flat inorganic compounds in the picture. The thickness of each flat inorganic compound in the picture is measured. Then, the arithmetic mean of the obtained thicknesses is calculated as the average thickness of the flat inorganic compound.

[0116] The average length of the flat inorganic compound is preferably 0.2 μm or more and 100.0 μm or less. When the average length is 0.2 μm or more, the flat inorganic compound is easily arranged in parallel with the paper substrate. In addition, when the average length is 100.0 μm or less, the possibility of a part of the flat inorganic compound protruding from the barrier layer is small. The average length of the flat inorganic compound is more preferably 30.0 μm or less, further preferably 15.0 μm or less, and particularly preferably 10.0 μm or less. The lower limit is more preferably 0.2 μm or more, more preferably 1.0 μm or more, and further preferably 3.0 μm or more.

[0117] Here, the average length of the flat inorganic compound in the state of being contained in the barrier layer is calculated as follows. An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set so that the screen contains about 20 to 30 flat inorganic compounds. The length (long diameter) of each flat inorganic compound in the screen is measured. Then, the arithmetic mean of the obtained lengths is calculated as the average length of the flat inorganic compound. It should be noted that the length of the flat inorganic compound is sometimes recorded as a particle size.

[0118] The average aspect ratio of the flat inorganic compound is 200 or more. When the average aspect ratio is 200 or more, it is easy to further improve the water vapor barrier property due to the labyrinth effect. The average aspect ratio of the flat inorganic compound is preferably 280 or more, more preferably 300 or more, further preferably 500 or more, and further preferably 800 or more. The larger the average aspect ratio, the more the permeation of water vapor is suppressed, and the more the water vapor barrier property is improved. In addition, the larger the average aspect ratio, the more the addition amount of the flat inorganic compound can be reduced.

[0119] The upper limit of the average aspect ratio is not particularly limited, but is preferably about 10,000 or less, more preferably about 5,000 or less, further preferably about 2,000 or less, and further preferably about 1,500 or less, from the viewpoint of the viscosity of the coating liquid.

[0120] Here, the average aspect ratio refers to a value obtained by dividing the average length of the flat inorganic compound obtained by taking an enlarged photograph of the cross section of the barrier layer using an electron microscope as described above and dividing the average thickness thereof.

[0121] Specific examples of the flat inorganic compound include mica of the mica group and brittle mica group, bentonite, kaolinite (kaolin mineral), pyrophyllite, talc, smectite, vermiculite, chlorite, brittle chlorite, serpentine, stilpnomelane, montmorillonite, and the like.

[0122] Among them, especially from the viewpoint of further improving water vapor barrier and gas barrier properties, it is preferred to contain one or more of mica and bentonite, and more preferably mica or bentonite. As specific examples of mica, synthetic mica (e.g., swelling mica, non-swelling mica), muscovite, sericite, phlogopite, biotite, fluorphlogopite (artificial mica), red mica, sodium mica, vanadium mica, illite, zinc mica, orange glass (Palagonite), brittle mica, etc. can be listed. In addition, as a specific example of bentonite, montmorillonite can be listed. They can be used alone or in combination of two or more.

[0123] The flat inorganic compound preferably includes a swelling layered silicate such as swelling mica. The barrier layer preferably includes hydroxy polyurethane and a swelling layered silicate. The swelling layered silicate is a layered inorganic compound that is swellable to water, and the layer is easily cleaved by shearing and has a nanometer-level thickness. By combining hydroxy polyurethane and swelling layered silicate, a thin swelling layered silicate with a high aspect ratio is dispersed in the hydroxy polyurethane resin film that originally has high water vapor barrier and gas barrier properties, thereby utilizing the maze effect to exert higher water vapor barrier and gas barrier properties.

[0124] Examples of the swelling layered silicate include sodium tetrasilicon mica, sodium hectorite, lithium taeniamite, fluorphlogopite, sodium montmorillonite, and the like.

[0125] The swellable layered silicate is preferably a swellable mica such as sodium tetrasilicon mica. Among commercially available swellable layered silicates, examples of swellable mica include NTS-10NC, NTO-05 (manufactured by Topy Industries), and Somasif ME300B-4T (manufactured by Katakura & Co-op Agri Corporation).

[0126] The content of the flat inorganic compound (preferably a swelling layered silicate) in the barrier layer is preferably 5.0 to 35.0% by mass, more preferably 10.0 to 25.0% by mass, and even more preferably 13.0 to 24.0% by mass. Within the above range, the water vapor barrier property and the gas barrier property are easily improved, and the heat sealability is also improved.

[0127] (Cationic resin)

[0128] The barrier layer contains a cationic resin in addition to the polyurethane resin and the flat inorganic compound. By using the flat inorganic compound and the cationic resin together, the gas barrier property and the water vapor barrier property, especially the water vapor barrier property, are greatly improved.

[0129] Preferably, the barrier layer contains hydroxy polyurethane, swelling layer silicate and cationic resin. This embodiment can exhibit very high water vapor barrier properties and gas barrier properties.

[0130] Since the surface of the flat inorganic compound (especially the swelling layer silicate) is easily charged to anionicity and the end face of the particle is easily charged to cationicity, the surface and the end face attract each other and easily form a card-house cohesive structure. By adding a cationic resin, the anionic groups on the surface of the particles can be blocked with cations, and the card-house cohesive structure can be destroyed. Therefore, the three-dimensional cohesion of the swelling layer silicate can be suppressed, and the swelling layer silicate can be arranged parallel to the plane of the paper substrate, and the maze effect can be fully exhibited. As a result, very high gas barrier properties and water vapor barrier properties can be exerted.

[0131] Specific examples of cationic resins include polyamide compounds, modified polyamide compounds, polyamine compounds, modified polyamine compounds, polyamide amine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide amine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, polyamide amine polyurea compounds, polyamide amine compounds, polyvinyl pyridine, amino-modified acrylamide compounds, polyvinylamine, polydiallyl dimethyl ammonium chloride, etc. These may be used alone or in combination of two or more.

[0132] Wherein, cationic resin is preferably selected from at least one of the group consisting of modified polyamide compound and modified polyamine compound, more preferably selected from at least one of the group consisting of modified polyamide resin and modified polyamine resin. As modified polyamide resin, commercially available modified polyamide resin can be used, for example, SPI203 (50) H, Tiangang Chemical Industry system, etc. can be enumerated. In addition, as modified polyamine resin, commercially available modified polyamine resin can also be used, for example, SEIKOAT T-EF501, Xingguang PMC system, etc. can be enumerated.

[0133] The content of the cationic resin in the barrier layer can be appropriately selected according to the type of materials used in the barrier layer such as hydroxy polyurethane and swellable layered silicate. From the viewpoint of further improving the barrier properties (especially gas barrier properties) and the viewpoint of heat sealability, the content of the cationic resin in the barrier layer is preferably 1.0 to 20.0% by mass, more preferably 1.0 to 10.0% by mass, further preferably 1.5 to 8.0% by mass, further preferably 1.8 to 5.0% by mass, and particularly preferably 2.0 to 3.0% by mass.

[0134] The surface charge of the cationic resin is preferably 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g, further preferably 0.1 to 4.0 meq / g, further preferably 0.1 to 2.0 meq / g, and particularly preferably 0.2 to 1.5 meq / g.

[0135] When the surface charge of the cationic resin is greater than or equal to the above lower limit, the effect of adding the cationic resin can be more fully obtained. On the other hand, when the surface charge is less than or equal to the above upper limit, the aggregation of the swelling layered silicate can be suppressed and the effect of the cationic resin can be more fully exerted.

[0136] It should be noted that the surface charge of the cationic resin is measured by the following method. First, the polymer as a sample is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. 0.001N sodium polyvinyl sulfonate is added dropwise to the solution using a charge analyzer Mutek PCD-04 (manufactured by BTG) to measure the charge.

[0137] The barrier layer may contain a dispersant, a surfactant, a defoaming agent, a wetting agent, a dye, a color tone adjuster, a thickener, etc. as needed to the extent that the above-mentioned specific barrier properties are not impaired.

[0138] (Barrier layer coating amount)

[0139] The coating amount of the barrier layer is not particularly limited, but is preferably 1 to 15 g / m2 as a solid content after drying from the viewpoint of barrier properties and re-dissociation properties. 2 , more preferably 2g / m2 More preferably, 10 g / m 2 Below, more preferably 8g / m 2 Below, more preferably 6g / m 2 the following.

[0140] The thickness of the barrier layer is preferably 1 to 20 μm, more preferably 2 to 10 μm.

[0141] (Method for forming barrier layer)

[0142] The method for forming the barrier layer is not particularly limited. For example, a barrier layer coating liquid is prepared by dispersing at least one resin selected from the group consisting of water-suspendable polymers and water-soluble polymers other than polyurethane resins, polyurethane resins, flat inorganic compounds, and cationic resins in a solvent. Preferably, the obtained barrier layer coating liquid is applied to a paper substrate and dried to form the barrier layer.

[0143] The solvent of the barrier layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not causing the problem of volatile organic solvents, the dispersion medium of the barrier layer coating liquid is preferably an aqueous medium, and more preferably water. In this specification, an aqueous medium refers to a medium containing 50% by mass or more of water.

[0144] The device for applying the barrier layer coating liquid is not particularly limited, and may be appropriately selected from commonly used coating devices. Examples thereof include: air knife coater, blade coater, gravure coater, rod blade coater, roll coater, reverse roll coater, Meyer rod coater, curtain coater, slot coater, Champlex coater, metering blade type size press coater, short dwell coater, spray coater, gate roll coater, lip coater, and other well-known coating devices.

[0145] <Sealing agent layer>

[0146] The barrier laminate further has a sealant layer on the side on which the barrier layer is laminated.

[0147] The sealant layer is a layer melted and bonded by heating, ultrasonic waves, etc. The sealant layer preferably contains a water-dispersible resin. As the water-dispersible resin, the above-mentioned substances as water-suspended polymers other than polyurethane resins can be listed, preferably polyolefin resins, styrene-acrylic acid copolymers, ethylene-(meth)acrylic acid copolymers and other acrylic resins, ethylene-vinyl acetate copolymers, polyester resins, rubber resins, polyurethane resins, polyamide resins, etc. They can be used alone or in combination of two or more. In addition, in addition to these resins, for the purpose of preventing adhesion and improving oil resistance, pigments such as silica and kaolin can also be added.

[0148] From the viewpoint of heat-sealing properties, the content of the water-dispersible resin in the sealant layer is preferably 70 to 99% by mass, more preferably 80 to 98% by mass, and even more preferably 92 to 98% by mass.

[0149] Preferably, the sealant layer is preferably a layer containing at least one resin selected from the group consisting of styrene-acrylic copolymers and polyolefin resins. As styrene-acrylic copolymers and polyolefin resins, the substances described in the above-mentioned water-suspended polymers can be used. As commercially available materials, aqueous dispersions of styrene-acrylic copolymers (product name: SEIKOAT RE-2016, product name: XP8829, manufactured by Starlight PMC), aqueous dispersions of polyolefin resins (product name: Rhobarr320, manufactured by Dow), etc. can be cited.

[0150] In the laminate of the present embodiment, the sealant layer contains wax. Due to the film-forming effect of the wax, very excellent water vapor barrier properties are exhibited. The wax is not particularly limited, and known waxes can be used.

[0151] From the viewpoint of high barrier properties, the wax preferably contains at least one selected from the group consisting of hydrocarbon waxes and ester waxes.

[0152] Examples of such waxes include the following. For example, natural waxes such as animal or plant-derived waxes (e.g., beeswax, carnauba wax, candelilla wax, etc.), mineral waxes, petroleum waxes (e.g., microcrystalline wax, etc.); synthetic waxes such as polyolefin waxes, paraffin waxes, and polyester waxes; and aliphatic ester waxes such as monoester waxes based on aliphatic monocarboxylic acids and aliphatic monohydric alcohols, diester waxes based on aliphatic monocarboxylic acids and aliphatic diols, and diester waxes based on aliphatic dicarboxylic acids and aliphatic monohydric alcohols. These may be used alone or in combination of two or more.

[0153] Among them, from the viewpoint of further improving the water vapor barrier property, it is preferred to contain at least one wax selected from the group consisting of paraffin wax, carnauba wax and microcrystalline wax. Carnauba wax may contain, for example, ester wax, hydrocarbon, etc. Polyolefin wax, paraffin wax, microcrystalline wax, etc. are equivalent to hydrocarbon wax.

[0154] The carnauba wax may be a synthetic product or a commercial product. Examples of the commercial product include Michem Lube-160RPH manufactured by Michelman Co., Ltd. and Selosol 524 manufactured by Chukyo Yushi Co., Ltd.

[0155] The paraffin wax may be either a synthetic product or a commercial product, and examples of the commercial product include AQUACER 497 manufactured by BYK and Hydrin L-700 manufactured by Chukyo Yushi Co., Ltd.

[0156] The microcrystalline wax may be a synthetic product or a commercial product. Examples of the commercial product include EMUSTAR-0001 manufactured by Nippon Seiro Co., Ltd.

[0157] As the polyethylene wax, either a synthetic product or a commercial product may be used. Examples of the commercial product include Aquacer 531 manufactured by BYK.

[0158] The sealant layer preferably contains a water-dispersible resin and wax. The content of the wax in the sealant layer is preferably 1 to 35 parts by mass, more preferably 2 to 20 parts by mass, further preferably 3 to 12 parts by mass, and further preferably 3 to 8 parts by mass relative to 100 parts by mass of the water-dispersible resin. By being within the above range, it is easy to take into account both water vapor barrier properties and gas barrier properties to a high degree, and thus the heat seal strength can also be improved. From the viewpoint of heat sealability, the content of the wax in the sealant layer is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and further preferably 2 to 8% by mass.

[0159] The sealant layer preferably contains a water-dispersible resin and a wax in at least any combination of the following (A) to (D).

[0160] (A) Water-dispersible resin: styrene-acrylic acid copolymer, wax: paraffin wax.

[0161] (B) Water-dispersible resin: styrene-acrylic acid copolymer, wax: carnauba wax.

[0162] (C) Water-dispersible resin: styrene-acrylic acid copolymer, wax: microcrystalline wax.

[0163] (D) Water-dispersible resin: polyolefin resin, wax: paraffin wax.

[0164] The sealant layer may contain other components in addition to the water-dispersible resin and wax. Examples of other components include pigments, dyes, crosslinking agents, coupling agents, surfactants, and water-soluble polymers, and known components may be used.

[0165] (Amount of sealant layer applied)

[0166] The coating amount of the sealant layer is not particularly limited, but is preferably 1 to 15 g / m2 as a solid content after drying from the viewpoint of heat sealability and re-dissociation properties. 2 Below, more preferably 2g / m 2 More preferably, 10 g / m 2 Below, more preferably 8g / m 2 Below, more preferably 6g / m 2 the following.

[0167] The thickness of the sealant layer is preferably 0.5 to 20 μm, more preferably 1 to 10 μm.

[0168] (Method for forming sealant layer)

[0169] The method for forming the sealant layer is not particularly limited. For example, a sealant layer coating liquid is prepared by dispersing a water-dispersible resin in a solvent. Preferably, the obtained sealant layer coating liquid is applied to the barrier layer and dried to form the sealant layer.

[0170] The solvent of the sealant layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not causing the problem of volatile organic solvents, the dispersion medium of the sealant layer coating liquid is preferably an aqueous medium, and more preferably water.

[0171] The total coating amount of the barrier layer and the sealant layer is preferably 12 g / m 2 Below, more preferably 11g / m 2 The above range means that even if the layer is thin, it can still exert very high gas barrier properties and water vapor barrier properties. In addition, by easily increasing the ratio of paper substrate within the above range, the product can be made lighter and the biodegradability can be further improved.

[0172] The lower limit of the coating amount is not particularly limited, but is preferably 2 g / m 2 More preferably 5g / m 2 More preferably, 8 g / m 2 above.

[0173] Therefore, the total coating amount of the barrier layer and the sealant layer is preferably 2 to 12 g / m 2 , more preferably 5 to 11 g / m 2 .

[0174] The heat seal peel strength of the sample obtained by heat-sealing the sealant layers of the laminate at 160°C, 0.2 MPa, and 1 second when the sealant layers of the laminate are peeled off using a tensile tester is preferably 2.0 N / 15 mm or more, more preferably 2.5 N / 15 mm or more, further preferably 2.8 N / 15 mm or more, and further preferably 3.0 N / 15 mm or more. By making the heat seal strength within the above range, bag breakage during transportation of the contents can be prevented.

[0175] The upper limit is not particularly limited, but is preferably 10.0 N / 15 mm or less, 7.0 N / 15 mm or less, 5.0 N / 15 mm or less, or 4.0 N / 15 mm or less.

[0176] Therefore, the heat seal peel strength is preferably 2.0 to 10.0 N / 15 mm.

[0177] <Manufacturing of laminated body>

[0178] The method for manufacturing the laminate is not particularly limited, and a known method can be used. The method for manufacturing the laminate has a step of first applying a barrier layer coating liquid on a paper substrate to form a barrier layer. Furthermore, there may be a step of applying a sealant layer coating liquid on the surface of the paper substrate on which the barrier layer is applied to form a sealant layer. The formation of each layer is as described above. It should be noted that each layer can be formed by applying and drying the coating liquid one by one, or by applying multiple layers simultaneously and then drying them.

[0179] The drying equipment for drying each coating layer is not particularly limited, and a known equipment can be used. Examples of the drying equipment include a hot air dryer, an infrared dryer, a gas burner, a hot plate, and the like.

[0180] The laminate comprises at least a paper substrate, a barrier layer and a sealant layer in this order. The barrier laminate may be a laminate consisting only of a paper substrate, a single-layer barrier layer and a sealant layer.

[0181] (Other layers)

[0182] The laminate of the present embodiment may also include layers other than the layers described above. For example, a pigment coating layer, an adhesive layer, a primer layer, etc. may also be included as needed. From the viewpoint of increasing the biomass ratio, it is preferred that an inorganic material layer such as an aluminum vapor deposition layer is not included.

[0183] <Pigment coating layer>

[0184] In the case where the laminate of the present embodiment has a barrier layer and a heat seal layer in sequence on one side of the paper substrate, a pigment coating layer may be provided on the other side of the paper substrate. By providing the pigment coating layer, the smoothness of the surface can be improved, and the friction force on the packaging machine parts such as the sailor collar can be reduced. As a result, a laminate having excellent printing adaptability and packaging processing adaptability can be obtained. The pigment coating layer preferably contains a pigment and an adhesive. From the viewpoint of exerting the above-mentioned effects, it is preferred to subject the pigment coating layer to a calendering treatment under arbitrary conditions.

[0185] The pigment contained in the pigment coating layer is not particularly limited, and examples thereof include: inorganic pigments such as kaolin, clay, engineered kaolin, exfoliated clay, calcined clay, heavy calcium carbonate, light calcium carbonate, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate, colloidal silica, satin white, etc.; organic pigments such as dense type, hollow type or core-shell type, etc. These may be used alone or in combination of two or more.

[0186] The content of the pigment in the pigment coating layer is not particularly limited, and is, for example, 50 to 85% by mass.

[0187] The binder contained in the pigment coating layer is not particularly limited, and examples thereof include: styrene-butadiene resins; acrylic resins such as (meth) acrylate copolymers and styrene-(meth) acrylic acid copolymers; olefin-unsaturated carboxylic acid copolymers such as ethylene-(meth) acrylic acid copolymers; natural polysaccharides such as dextrin, mannan, chitosan, arabinogalactan, glycogen, inulin, pectin, hyaluronic acid, hydroxyethylated starch, oxidized starch, etherified starch, phosphated starch, enzyme-modified starch, and modified starch obtained by flash drying thereof, and oligomers thereof, and modified products thereof, etc. These may be used alone or in combination of two or more.

[0188] The content of the binder in the pigment coating layer is not particularly limited, and is, for example, 5 to 50% by mass.

[0189] The pigment coating layer may contain ingredients such as a binder, a dispersant, a thickener, a water retaining agent, a defoaming agent, a water resistance agent, a colorant, and a surfactant in addition to the pigment and the binder.

[0190] The coating amount of the pigment coating layer (converted into solid content) is not particularly limited, and is, for example, 3 to 30 g / m 2 The method for forming the pigment coating layer is not particularly limited, but a method in which a dispersion containing a pigment and a binder is applied to a paper substrate and then dried is preferred.

[0191] (Barrier properties of laminated body)

[0192] The water vapor permeability of the barrier laminate of the present embodiment measured under the conditions of 40° C. and 90% RH in accordance with JIS-Z-0208:1976 is preferably less than 50 g / m 2 The water vapor permeability is more preferably 30 g / m 2 ·Day or less, more preferably 20g / m 2 ·Day or less, more preferably 15g / m 2 ·Day or less, especially preferably 10g / m 2 ·Day or less, particularly preferably 8g / m 2 ·Day or less, 6g / m is very preferred 2 ·Day or less. Within the above range, the water vapor barrier property is very high.

[0193] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0 g / m 2 · More than 1g / m 2 · More than 2g / m 2 The water vapor permeability can be controlled by, for example, the thickness of the barrier layer and the selection of the ingredients contained in the barrier layer.

[0194] Therefore, the water vapor permeability is preferably 0 g / m 2 ·More than day and less than 50g / m 2 day, can also be 1 to 30 g / m 2 ·day.

[0195] Furthermore, the oxygen permeability of the laminate at 23°C and 50% RH is preferably 10.0 mL / m 2 ·day·atm or less. The oxygen permeability is preferably 8.0 mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, more preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less, particularly preferably 0.6L / m 2 ·day·atm or less. Within the above range, the oxygen barrier property is very high.

[0196] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m2 ·day·atm or more. The oxygen permeability can be controlled by, for example, the thickness of the barrier layer and the selection of the components contained in the barrier layer.

[0197] Therefore, the oxygen permeability is preferably 0.0 to 10.0 mL / m 2 ·day·atm, can also be 0.1~8.0mL / m 2 ·day·atm.

[0198] Furthermore, the oxygen permeability of the laminate at 23°C and 85% RH is preferably 10.0 mL / m 2 ·day·atm or less, more preferably 8.0mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, particularly preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less.

[0199] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more.

[0200] Therefore, the oxygen permeability is preferably 0.0 to 10.0 mL / m 2 ·day·atm, can also be 0.1~8.0mL / m 2 ·day·atm.

[0201] The oxygen permeability at 85% RH satisfying the above range indicates that sufficient gas barrier properties are exhibited even in a high humidity environment. The oxygen permeability at 85% RH can be set to the above range by selecting the material used in the barrier layer.

[0202] (Ratio of paper base material weight)

[0203] In the laminate of the present embodiment, the ratio of the weight of the paper base material is a value obtained by calculating the percentage as follows based on the total weight of the laminate.

[0204] (Ratio of the weight of the paper substrate) = (weight of the paper substrate) / (weight of the laminate) × 100

[0205] The weight ratio of the paper substrate is preferably 75% or more, more preferably 80% or more, and further preferably 82% or more. When the weight ratio of the paper substrate is above the lower limit, a laminate having a high biomass ratio and reduced environmental load can be provided. The upper limit is not particularly limited, but is usually 99% or less, preferably 95% or less. Therefore, the weight ratio of the paper substrate is preferably 75% to 99%.

[0206] The laminate has very high water vapor barrier and gas barrier properties, and therefore can be suitable for use as a paper processed product. As paper processed products, packaging bags, paper containers, paper cups, etc. can be listed. In addition, the laminate can be suitable for use as paper processed products such as packaging materials for food, cosmetics, daily sundries, medical products, electronic components, etc. The laminate can also be suitable for use as paper processed products such as packaging materials for contents with fragrance / odor. In addition, it can also be suitable for use as paper processed products such as packaging materials for food, cosmetics, daily sundries, medical products, electronic components, etc. exposed to high humidity conditions. The laminate can also be a barrier laminate.

[0207] The packaging bag can be obtained by bending or stacking two sheets of the barrier laminate of the present embodiment so that the heat-sealing layers face each other and heat-sealing the peripheral edges thereof. Examples of the packaging bag include standing pouch, side seal, double-side seal, three-side seal, four-side seal, envelope seal, butt seal (pillow seal), pleat seal, flat bottom seal, square bottom seal, gusset, and the like.

[0208] Example

[0209] In order to specifically illustrate the present invention, examples are given below, but the present invention is not limited to these examples. It should be noted that, unless otherwise specified, the following operations are performed at 25° C. and a relative humidity of 50% RH. In addition, “parts” and “%” in the examples and comparative examples represent “parts by mass” and “% by mass”, respectively, unless otherwise specified.

[0210] Example 1

[0211] To 33.3 parts of an aqueous dispersion of a flat inorganic compound (swellable mica, average thickness 5 nm, average length (major diameter) 6.3 μm, average aspect ratio 1260, solid content concentration 6 mass %, product name: NTS-10NC, manufactured by Topy Industries), 5.1 parts of a self-emulsifying emulsion of an ethylene-acrylic acid copolymer (solid content concentration 29.2 mass %, product name: ZAIKTHENE AC, manufactured by Sumitomo Seika Chemicals) were added while stirring, and further 26.7 parts of a self-emulsifying aqueous emulsion of a hydroxy polyurethane (solid content concentration 30 mass %, product name: HPU-W013A, manufactured by Dainichi Seika Industries, hydroxyl value 235 mgKOH / g, acid value 30 mgKOH / g, glass transition temperature 70°C) were added and stirred.

[0212] 0.57 parts of modified polyamide resin (surface charge 0.4 meq / g, solid content concentration 53% by mass, product name: SPI203 (50) H, manufactured by Taoka Chemical Industry) was added thereto and stirred. 5.0 parts of an aqueous solution obtained by dissolving ethylene-modified polyvinyl alcohol (product name: EXCEVAL RS-1717, manufactured by Kuraray Co., Ltd.) as a water-soluble polymer in water at a solid content concentration of 10% by mass was further added. 0.30 parts of a 25% by mass ammonia aqueous solution was further added and stirred. Furthermore, dilution water was added to adjust the solid content concentration to 19% by mass to prepare a barrier layer coating.

[0213] To 90.9 parts of a styrene-acrylic copolymer aqueous dispersion (solid content concentration 33% by mass, product name: SEIKOAT RE-2016, manufactured by Seiko PMC), 3 parts of a paraffin emulsion (solid content concentration 50% by mass, product name: AQUACER 497, manufactured by BYK) were added, and the mixture was diluted with water to a solid content concentration of 22% by mass to prepare a sealant layer coating.

[0214] The barrier layer coating is prepared at a solid content of 5 g / m 2 Coated on paper substrate 50g / m 2 One side of the paper was dried by air at 120°C for 1 minute. The solid content of the barrier layer was 5 g / m 2 After applying the sealant layer coating in a manner of , it was dried by air blowing at 120° C. for 1 minute to obtain a heat-sealable laminate.

[0215] Example 2

[0216] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer of the barrier layer coating material was changed to 13.7 parts and the self-emulsifying aqueous emulsion of hydroxy polyurethane was changed to 20.0 parts.

[0217] Example 3

[0218] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of swelling mica in the barrier layer coating material was changed to 50 parts.

[0219] Example 4

[0220] The paper base material was set to 70 g / m 2 A heat-sealable laminate was obtained in the same manner as in Example 1 except that unbleached kraft paper (unbleached light packaging paper, manufactured by Oji Materia Co., Ltd.) was used.

[0221] Example 5

[0222] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of the cationic resin in the barrier layer coating material was changed to 1.89 parts.

[0223] Example 6

[0224] A heat-sealable laminate was obtained in the same manner as in Example 1 except that 0.60 parts of a modified polyamine resin (surface charge 1.3 meq / g, solid content 50 mass %, product name: SEIKOAT T-EF501, manufactured by Seiko PMC) was used as the cationic resin of the barrier layer coating.

[0225] Example 7

[0226] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was replaced with 3.8 parts of a styrene-acrylic acid copolymer adhesive (solid content concentration: 39 mass %, product name: JONCRYL HSL-9012, manufactured by BASF).

[0227] Example 8

[0228] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was replaced with 3.3 parts of an acid-modified styrene-butadiene copolymer (SBR) adhesive (solid content concentration 46% by mass, product name: LX407S12, manufactured by ZEON Corporation of Japan).

[0229] Example 9

[0230] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 6.5 parts of a polyolefin resin adhesive (solid content concentration: 23% by mass, product name: HYDRECT HS, manufactured by DIC Corporation).

[0231] Example 10

[0232] A heat-sealable laminate was obtained in the same manner as in Example 1 except that 10.0 parts of an aqueous solution prepared by dissolving ethylene-modified polyvinyl alcohol in water so as to have a solid content concentration of 10% by mass was added.

[0233] Embodiment 11

[0234] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the ethylene-modified polyvinyl alcohol was changed to 10.0 parts of an aqueous solution of ammonium polyacrylate (solid content concentration 30% by mass, product name: Aron A-30, manufactured by Toagosei Co., Ltd.) adjusted to a solid content concentration of 5% by mass.

[0235] Example 12

[0236] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the styrene-acrylic acid copolymer aqueous dispersion of the sealant layer coating was changed to 73.2 parts of a polyolefin aqueous dispersion (solid content concentration 43 mass %, product name: Rhobarr 320, manufactured by Dow).

[0237] Example 13

[0238] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of the paraffin emulsion was changed to 1.8 parts.

[0239] Embodiment 14

[0240] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of the paraffin emulsion was changed to 6.0 parts.

[0241] Embodiment 15

[0242] A heat-sealable laminate was obtained in the same manner as in Example 1 except that 6.0 parts of carnauba wax (solid content concentration: 25% by mass, product name: Michem Lube-160RPH, manufactured by Michelman Co., Ltd.) was used instead of the paraffin wax emulsion.

[0243] Example 16

[0244] The flat inorganic compound was changed from swelling mica to bentonite (sodium montmorillonite) (average thickness 1 nm, average length (major diameter) 0.3 μm, average aspect ratio 300, product name: KUNIPIA G, manufactured by KUNIMINE INDUSTRIES), adjusted to an aqueous dispersion with a solid content concentration of 10% by mass, and 20.0 parts were added. Except for this, a heat-sealable laminate was obtained in the same manner as in Example 1.

[0245] Embodiment 17

[0246] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the swelling mica in the barrier layer coating material was changed to 100 parts and the cationic resin was changed to 5.7 parts.

[0247] Embodiment 18

[0248] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of paraffin in the sealant layer coating was changed to 18.0 parts.

[0249] Embodiment 19

[0250] A heat-sealable laminate was obtained in the same manner as in Example 1 except that 3.8 parts of microcrystalline wax (solid content concentration: 40 mass %, product name: EMUSTAR-0001, manufactured by Nippon Seira Co., Ltd.) was used instead of the paraffin wax emulsion.

[0251] Embodiment 20

[0252] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying aqueous emulsion of hydroxy polyurethane (solid content concentration 30% by mass, product name: HPU-W013A, manufactured by Dainichi Seika Industries) of the barrier layer coating was replaced with a dispersion of polyurethane having a structural unit derived from meta-xylylene diisocyanate (solid content concentration 30% by mass, product name: TAKELAC WPB-341(30), manufactured by Mitsui Chemicals). 1 As a result of H-NMR measurement, the content of the structural unit derived from meta-xylylene diisocyanate was 50 mol% or more relative to the total amount of the structural unit derived from the polyisocyanate. The polyurethane resin had a glass transition temperature of 130°C.

[0253] Comparative Example 1

[0254] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer of the barrier layer coating material was changed to 32.5 parts and the self-emulsifying aqueous emulsion of hydroxy polyurethane was changed to 0 part.

[0255] Comparative Example 2

[0256] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the swelling mica in the barrier layer coating material was changed to 0 parts.

[0257] Comparative Example 3

[0258] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the cationic resin in the barrier layer coating material was changed to 0 part.

[0259] Comparative Example 4

[0260] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the amount of paraffin in the sealant layer coating material was changed to 0 parts.

[0261] Comparative Example 5

[0262] The flat inorganic compound was changed from swelling mica to engineered kaolin (average thickness 100 nm, average length 9 μm, average aspect ratio 90, product name: BARRISURF HX, manufactured by Imerys), and an aqueous dispersion having a solid content concentration of 50% by mass was added in 4.0 parts. A heat-sealable laminate was obtained in the same manner as in Example 1, except that this was repeated.

[0263] Comparative Example 6

[0264] 90.0 parts of acid-modified SBR latex (LX407 S12) and 9.4 parts of acid-modified SBR latex (LX407BP-6) as anionic binders were added to 47.3 parts of aqueous dispersion of layered inorganic compound (swellable mica, NTO-05) while stirring. 4.5 parts of modified polyamide resin (SPI203 (50)) as cationic resin was added thereto and stirred. Furthermore, 0.6 parts of 25% ammonia solution was added and stirred. Furthermore, dilution water was added to adjust the solid content concentration to 32% to prepare a coating liquid for a water vapor barrier layer.

[0265] An aqueous solution of polyvinyl alcohol (PVA, POVAL PVA117) as a water-soluble polymer with a solid content concentration of 10% was prepared to prepare a coating liquid for the gas barrier layer.

[0266] The obtained water vapor barrier layer coating liquid was dried so that the coating amount of the water vapor barrier layer became 13 g / m 2 The coating was applied on one side of single gloss white kraft paper using a Meyer rod and then dried in a hot air dryer at 120°C for 1 minute to form a water vapor barrier layer.

[0267] Furthermore, on the water vapor barrier layer, the gas barrier layer was applied in an amount of 2.0 g / m after drying. 2The coating liquid for the gas barrier layer was applied by a Meyer bar, and then dried in a hot air dryer at 120° C. for 1 minute to form a gas barrier layer.

[0268] Furthermore, the solid content on the surface where the oxygen barrier layer was formed was 5 g / m 2 A water-based heat sealant (Chemipearl S-300, manufactured by Mitsui Chemicals, Inc.) was applied in a manner to form a sealant layer (thickness: 5 μm) to obtain a gas barrier laminate.

[0269] The following evaluations were performed on the obtained laminated bodies of Examples 1 to 18 and Comparative Examples 1 to 6. The results are shown in Tables 1 to 3.

[0270] [Oxygen permeability]

[0271] The oxygen permeability of the laminate was measured using an oxygen permeability measuring device (MOCON Co., Ltd., OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50%. Specifically, 5 g / m 2 After an isocyanate adhesive (manufactured by DIC Corporation, 10 parts of DICDRY LX-500 and 1 part of DICDRY KW-75 were mixed accordingly), a CPP film (manufactured by Hokuetsu Chemical Co., Ltd., GP-32) having a thickness of 20 μm was laminated to form a laminated sheet.

[0272] For the laminated sheet, the oxygen permeability at a temperature of 23°C and a relative humidity of 50% and at a temperature of 23°C and a relative humidity of 85% was measured in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property. It should be noted that the laminated CPP film is not affected by the unevenness of the laminate and is easy to measure, and the CPP film does not affect the oxygen permeability.

[0273] [Water vapor transmission rate]

[0274] The water vapor permeability of the laminate was measured in accordance with JIS-Z-0208:1976 (cup method) B method (40°C±0.5°C, relative humidity 90%±2%), with the sealant layer on the inner side.

[0275] [Ratio of paper base material weight]

[0276] The weight ratio of the paper substrate is based on the total weight of the laminate, and the percentage is calculated as follows.

[0277] (Ratio of the weight of the paper substrate) = (weight of the paper substrate) / (weight of the laminate) × 100

[0278] [Determination of heat seal peel strength]

[0279] Two sets of laminates were overlapped in a manner that the coating layers were facing each other, and heat-sealed using a heat seal tester (manufactured by TESTER SANGYO, TP-701-B) at 160°C, 0.2MPa, and 1 second. The heat-sealed test piece was left to stand for more than 4 hours in a room at a temperature of 23°C ± 1°C and a humidity of 50% ± 2%. Next, the heat-sealed test piece was cut into 15 mm wide pieces, and a tensile tester was used to perform T-peeling at a tensile speed of 300 mm / min, and the maximum load recorded was taken as the heat seal peel strength (N / 15mm).

[0280] The formulations of the barrier layer and the sealant layer in Tables 1 to 3 indicate the weight percentage of the solid content. 2 , B means using unbleached kraft paper 70g / m 2 .

[0281] [Table 1]

[0282]

[0283] [Table 2]

[0284]

[0285] [Table 3]

[0286]

Claims

1. A laminate, wherein: The laminate comprises: a paper substrate layer, a barrier layer and a sealant layer in order, The barrier layer comprises a polyurethane resin, a flat inorganic compound having an average thickness of 50 nm or less and an average aspect ratio of 200 or more, and a cationic resin. The sealant layer comprises wax.

2. The laminate according to claim 1, wherein The polyurethane resin includes at least one selected from the group consisting of polyurethane having a structural unit derived from meta-xylylene isocyanate and hydroxy polyurethane.

3. The laminate according to claim 1 or 2, wherein: The flat inorganic compound includes a swelling layered silicate.

4. The laminate according to any one of claims 1 to 3, wherein The barrier layer contains 1.0 to 20.0 mass % of the cationic resin.

5. The laminate according to any one of claims 1 to 4, wherein The barrier layer contains 30.0 to 80.0 mass % of the polyurethane resin.

6. The laminate according to any one of claims 1 to 5, wherein The barrier layer contains 5.0 to 35.0 mass % of the flat inorganic compound.

7. The laminate according to any one of claims 1 to 6, wherein The barrier layer further comprises at least one selected from the group consisting of a water-suspendable polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, The water-suspendable polymer comprises at least one selected from the group consisting of styrene-butadiene copolymers, styrene-acrylic acid copolymers, olefin-unsaturated carboxylic acid copolymers and polyolefin resins. The water-soluble polymer includes at least one selected from the group consisting of vinyl alcohol polymers and (meth)acrylic acid polymers.

8. The laminate according to any one of claims 1 to 6, wherein The barrier layer further comprises a water-suspendable polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, The barrier layer comprises the water-suspendable polymer and the water-soluble polymer in any combination of at least the following (A) to (E), (A) Water-suspended polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol; (B) Water-suspended polymer: ethylene-acrylic acid copolymer, water-soluble polymer: polyacrylic acid; (C) Water-suspended polymer: styrene-acrylic acid copolymer, water-soluble polymer: polyvinyl alcohol; (D) water-suspendable polymer: styrene-butadiene copolymer, water-soluble polymer: polyvinyl alcohol; and (E) Water-suspended polymer: polyolefin resin, water-soluble polymer: polyvinyl alcohol.

9. The laminate according to claim 7 or 8, wherein The barrier layer contains 1.0 to 50.0% by mass of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin in total.

10. The laminate according to any one of claims 7 to 9, wherein The ratio of the mass of the polyurethane resin in the barrier layer to the total mass of the water-suspended polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin, i.e., the mass of the polyurethane resin: the total mass of the water-suspended polymer and the water-soluble polymer, is 50:50 to 95:

5.

11. The laminate according to any one of claims 1 to 10, wherein The sealant layer includes a water-dispersible resin.

12. The laminate according to any one of claims 1 to 11, wherein The wax includes at least one selected from the group consisting of hydrocarbon waxes and ester waxes.

13. The laminate according to any one of claims 1 to 12, wherein The wax includes at least one selected from the group consisting of paraffin wax, carnauba wax, and microcrystalline wax.

14. The laminate according to any one of claims 1 to 13, wherein The sealant layer comprises a water-dispersible resin, The water-dispersible resin includes at least one selected from the group consisting of styrene-acrylic acid copolymers and polyolefin resins.

15. The laminate according to any one of claims 1 to 14, wherein The sealant layer comprises a water-dispersible resin, The sealant layer comprises the water-dispersible resin and the wax in at least any combination of the following (A) to (D), (A) water-dispersible resin: styrene-acrylic acid copolymer, wax: paraffin; (B) water-dispersible resin: styrene-acrylic acid copolymer, wax: carnauba wax; (C) water-dispersible resin: styrene-acrylic acid copolymer, wax: microcrystalline wax; and (D) Water-dispersible resin: polyolefin resin, wax: paraffin wax.

16. The laminate according to any one of claims 1 to 15, wherein The sealant layer comprises a water-dispersible resin, The content of the wax in the sealant layer is 1 to 35 parts by mass based on 100 parts by mass of the water-dispersible resin.

17. The laminate according to any one of claims 1 to 16, wherein The content of the wax in the sealant layer is 1 to 30% by mass.

18. A processed paper product, produced using the laminate according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Packaging paper

    JP2021138434A

  • Gas barrier laminate and method for producing same

    US20210310194A1

  • Barrier laminate

    WO2021106891A1